THE ADMINISTRATIVE LAW ASPECTS OF PHYSICAL PLANNING IN THE REPUBLIC OF SERBIA- BUILDING PERMIT ISSUING PROCEDURE - Martinović, Aleksandar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
One of the fundamental characteristics of the administrative law norms is its multiplicity. Alongside the General Part of the Administrative Law (legal norms applying to the administrative bodies including legal situations when all the administrative bodies act), an important part of legal order of every country, thus of the Republic of Serbia as well, are the norms falling within special part of the Administrative law, regulating different areas of social life, as well as the competences of the certain administrative bodies in those areas. Legal regulation of physical planning is among the most important areas of social life and it draws particular attention of the modern states. In legal order of the Republic of Serbia, this area is one of the most crucial when it comes to the special part of administrative law norms apperance. Out of all the issues regulated by these norms, there are three exceptionally important: building permit issuing procedure, legalization procedure and the procedure of building land conversion. Each represents a special administrative procedure.